2005
DOI: 10.1007/11566489_18
|View full text |Cite
|
Sign up to set email alerts
|

Soft-Tissue Motion Tracking and Structure Estimation for Robotic Assisted MIS Procedures

Abstract: Abstract. In robotically assisted laparoscopic surgery, soft-tissue motion tracking and structure recovery are important for intraoperative surgical guidance, motion compensation and delivering active constraints. In this paper, we present a novel method for feature based motion tracking of deformable soft-tissue surfaces in totally endoscopic coronary artery bypass graft (TECAB) surgery. We combine two feature detectors to recover distinct regions on the epicardial surface for which the sparse 3D surface geom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
99
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 114 publications
(99 citation statements)
references
References 15 publications
(15 reference statements)
0
99
0
Order By: Relevance
“…This method has been used for registering endoscopic video images to biomechanical models of the liver. Another technique also operating at near real-time frame rates that uses local optimization to propagate disparity information around correspondence seeds obtained using feature matching as developed in (Stoyanov et al, 2005b) has also been shown to perform well for endoscopic images . This method has the desirable property of ignoring regions with highlights, occlusions or high uncertainty and has also recently been extended to recover temporal motion as well as 3D shape (Stoyanov, 2012a).…”
Section: Application To Laparoscopymentioning
confidence: 99%
“…This method has been used for registering endoscopic video images to biomechanical models of the liver. Another technique also operating at near real-time frame rates that uses local optimization to propagate disparity information around correspondence seeds obtained using feature matching as developed in (Stoyanov et al, 2005b) has also been shown to perform well for endoscopic images . This method has the desirable property of ignoring regions with highlights, occlusions or high uncertainty and has also recently been extended to recover temporal motion as well as 3D shape (Stoyanov, 2012a).…”
Section: Application To Laparoscopymentioning
confidence: 99%
“…Optical techniques for laparoscopic 3-D surface reconstruction can roughly be divided into two categories [47]. Passive methods, such as stereoscopy [48]), shape-from-shading [49], shape-from-motion (SfM) [50], and simultaneous localization and mapping (SLAM) [51] need only endoscopic RGB images as input. Active methods, such as structured light [52,53] and ToF require controlled light to be projected into the environment.…”
Section: -D Endoscopy For Minimally Invasive Proceduresmentioning
confidence: 99%
“…However, this method is only applied for 2D tracking without extraction of depth information. Tracking the heart motion in stereo endoscopic beating heart sequences is proposed in [7][8][9][10]. However, these approaches are sensitive to visual artifacts and variations in illumination.…”
Section: Related Workmentioning
confidence: 99%